Hula hoop game: its use and implication for physical fitness - Rohman, Ujang (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2019)
The study aims at identifying and confirming the influence of the hula hoop game conduct on the level of physical fitness. Within the conduct of the study, the researcher implemented the experiment method while the nature of the study was a quantitative study with systematic and structured implementation by describing the influence of the independent variable (X) on the independent variable (Y). Then, the population of the study was the students of Sawahan IV Public Elementary School Surabaya while the samples that had been selected for the study were the female students from the higher degree (Grade 4, 5 and 6) who had been selected proportionally based on the strata; the overall number of the sample was 40 students. The results of the hypothesis test analysis on the actual rate (α = 0.05) and the degree of skewness = 39 show that the t-count value for each component of physical fitness is higher than the t-table value; in other words, t-count > t-table with sig. = 0.05. The implication is that the implementation of hula hoop game learning displays significant influence on each component of physical fitness namely speed, strength, flexibility, agility, power and endurance. On the other hand, the results of variance test (F-test) analysis on the actual rate (α = 0.05) show that the F-count is higher than the F-table namely 2.24 > 2.17; in other words, F-count > F-table with the sig. 0.05 (6:133). Thus, the implication is that the implementation of the hula hoop game has significant influence on the level of physical fitness. In brief, the conclusion that might be drawn from the study is that the hula hoop game is very effective for improving the level of physical fitness especially for the elementary school students.